2004
DOI: 10.1111/j.1442-2042.2004.00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary malignancies in Japanese patients with renal cell carcinoma

Abstract: Aim : To evaluate the incidence, nature and prognosis of multiple primary malignancies involving renal cell carcinoma (RCC) in Japan. Methods : Between 1975 and 1998, 319 patients underwent an operation for RCC at Hokkaido University, Sapporo, Japan. The incidence of other primary malignancies was determined and classified as antecedent, synchronous or subsequent. Follow-up was obtained by thorough chart review or telephone interview, and ranged from 0 to 276 months (median 49.0 months). To analyze the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 18 publications
9
44
2
4
Order By: Relevance
“…RCC is the most common tumor found to coexist with other malignancies [1,10,12,13,14]. In different studies the incidence of second primary malignancy associated with RCC is reported to be 12%-27.4% [1,10,11,14]. About 19% of these tumors appeared synchronously [1].…”
Section: Discussionmentioning
confidence: 99%
“…RCC is the most common tumor found to coexist with other malignancies [1,10,12,13,14]. In different studies the incidence of second primary malignancy associated with RCC is reported to be 12%-27.4% [1,10,11,14]. About 19% of these tumors appeared synchronously [1].…”
Section: Discussionmentioning
confidence: 99%
“…All these associations can be metachronous (develop consequently) or synchronous (tumors coexist at the time of diagnosis). Synchronous breast and renal cell carcinoma (RCC) can occur rarely [3]. We hereby report a case of carcinoma breast with synchronous renal cell carcinoma.…”
Section: Introductionmentioning
confidence: 93%
“…Renal cancer is known to be associated with multiple tumors involving bladder, prostate, rectum, lung, non-Hodgkin's lymphoma, stomach and melanoma etc. [3]. Breast cancer is also associated with increased risk of second tumor involving colon, vulva, lung, larynx, liver, uterus and thyroid [4].…”
Section: Introductionmentioning
confidence: 99%
“…Haraguchi et al conducted a single-institution retrospective analysis of multiple primary malignancies with NSCLC and reported gastric cancer to be the most prevalent neoplasm (33 of 938 patients) (17). In addition, Sato et al evaluated the incidence of multiple primary malignancies involving renal cell carcinoma (319 patients) and found that the most common other malignancy was gastric cancer (11 of 319 patients) (23). However, because gastric cancer is the most frequent malignancy in men and the third most common neoplasm in women in Japan, these results may simply reflect the epidemiological prevalence of this disease.…”
Section: Discussionmentioning
confidence: 99%